1989
DOI: 10.1530/jrf.0.0850229
|View full text |Cite
|
Sign up to set email alerts
|

Does inadequate luteal function limit the establishment of pregnancy in the early post-partum ewe?

Abstract: observed in 2 of 7 (0\m=.\28)lactating and 4 of 9 (0\m=.\44)early weaned ewes compared with corresponding values of 1 of 13 (0\m=.\08) and 2 of 11 (0\m=.\18) in the 35-day post-partum group. Luteal function was normal in all standard ewes. The proportion of successful pregnancies in the standard ewes was 0\m=.\80 (12 of 15) compared with 0 in lactating and early weaned ewes in the 21-day group and 0\m=.\08 (1 of 13) and 0\m=.\36 (4 of 11) respectively in the 35-day group.The incidence of inadequate luteal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The results of our present study show that the incidence of luteal inadequacy, as assessed by peripheral progesterone concentrations, was greater in early weaned than in lactating ewes and confirms our earlier observation that the suckling stimulus per se does not contribute to abnormal luteal function in early post-partum ewes induced to ovulate during the non-breeding and breeding seasons (Wallace et al, 1989a). In earlier studies using lactating ewes, inadequate luteal function following induction of ovulation 28 days post partum was associated with complete failure of fertili¬ zation and low embryo recovery rates on Day 6 after oestrus (Wallace et al, 1989b).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our present study show that the incidence of luteal inadequacy, as assessed by peripheral progesterone concentrations, was greater in early weaned than in lactating ewes and confirms our earlier observation that the suckling stimulus per se does not contribute to abnormal luteal function in early post-partum ewes induced to ovulate during the non-breeding and breeding seasons (Wallace et al, 1989a). In earlier studies using lactating ewes, inadequate luteal function following induction of ovulation 28 days post partum was associated with complete failure of fertili¬ zation and low embryo recovery rates on Day 6 after oestrus (Wallace et al, 1989b).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, none of these post-partum ewes maintained their pregnancies after autotransfer. In a subsequent study (Wallace et al, 1989a) we demonstrated that good quality Day-5 embryos donated from ewes in which the interval from parturition was in excess of 150 days had a very low survival rate when transferred into the uterine environment of the early post-partum ewe (0 pregnancies in 16 ewes induced to ovulate 21 days post partum and 5 pregnancies in 24 ewes induced to ovulate 35 days post partum). In contrast, the results of the present study show that embryos recovered on Day 3 after oestrus from ewes inseminated between 24 and 29 days post partum are viable when transferred to a normal uterine environment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, we have previously shown that the induction of ovulation during the post-partum period is associated with a high incidence of prematurely regressing corpora lutea which is independent of the suckling stimulus but dependent on the stage post par¬ tum (Wallace, Robinson & Aitken, 1989a;Wallace, Robinson, McKelvey & Aitken, 1989c). A large body of circumstantial evidence suggests that these prema¬ turely regressing corpora lutea result from enhanced or premature release of prostaglandin F2a (PGF2a) from the uterus (Troxel & Kesler, 1984; Copelin, Smith, Garverick & Youngquist, 1987;Lewis & Bolt, 1987;Copelin, Smith, Keisler & Garverick, 1989;Schirar, Meusnier, Paly et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evi dence indicates that the suckling-induced release of β-endorphins, which inhibit the release of GnRH, is responsible for the inhibition of ovarian func tion. [153][154][155] Ewes, [156][157][158] cows, [159][160][161][162] sows, 163,164 and does 165 can be induced to return to cyclic ovarian function (provided they have not become seasonally anestrous) by weaning of the young. In cattle, wean ing for a period as short as 2 days will induce estrus in a large percentage of the cows.…”
mentioning
confidence: 99%